Aerial Survey Estimates of Abundance of the Eastern Chukchi Sea Stock of Beluga Whales (Delphinapterus leucas) in 2012 - Lowry, Lloyd F.; Kingsley, Michael C.S.; Hauser, Donna D.W.; Clarke, Janet; Suydam, Robert (ARCTIC, 2017)
The eastern Chukchi Sea (ECS) stock of beluga whales is one of three stocks in western Alaska that are co-managed by the National Marine Fisheries Service and the Alaska Beluga Whale Committee. Abundance of this stock was estimated as 3710 in 1991 from incomplete data. Analysis of data from satellite-linked time-depth recorders (SDRs) attached to belugas in summer concentration areas of the ECS and Beaufort Sea (BS) stocks provided an overview of beluga distribution and movements and allowed the identification of an area (140˚ W to 157˚ W in the BS) and a time period (19 July – 20 August) in which the distributions of the two stocks do not overlap. Aerial survey data were collected by the Aerial Surveys of Arctic Marine Mammals (ASAMM) project in that region and time period in 2012. We used those data in a line transect analysis that estimated there were 5547 (CV = 0.22) surface-visible belugas in the study area. Data from SDRs were used to develop correction factors to account for animals that were missed because they were either outside of the study area or diving too deep to be seen, resulting in a total abundance estimate of 20 752 (CV = 0.70). The average annual Alaska Native subsistence harvest from the ECS stock (57) is about 0.3% of the population estimate. Without data collected by the ASAMM project and from satellite-linked tags, this analysis would not have been possible. Additional surveys and tagging of ECS belugas are warranted. Le stock de bélugas de l’est de la mer des Tchouktches (EMT) figure parmi les trois stocks de l’ouest de l’Alaska à être gérés conjointement par le National Marine Fisheries Service et l’Alaska Beluga Whale Committee. À partir de données incomplètes, l’abondance de ce stock a été estimée à 3 710 en 1991. L’analyse des données recueillies à l’aide d’enregistreurs de profondeur temporelle satellitaires (SDR) fixés aux bélugas dans les zones de concentration estivales de l’EMT et de la mer de Beaufort (MB) a permis d’obtenir un aperçu de la répartition et du déplacement des ...